The Influence Of The Implementation Of Good Corporate Governance On The Quality Of Financial Performance At Muamalat Bank In Sorong District In 2018-2022 - Lidya Aprilia Jumroh (UNIVED Press, 2024)
This study aims to analyze and determine the effect of GCG implementation, Islamic financial performance, and the influence of GCG implementation on Islamic financial performance at Bank Muamalat in Sorong Regency. This research is a quantitative research using associative, using secondary data sources derived from record evidence, or historical reports that have been compiled in archives both published and unpublished. So that this research was obtained from Bank Muamalat's financial statements, annual reports and GCG reports for the 2018-2022 period which were published publicly in the Indonesian Banking Directory and the official website of each Muamalat bank. The results of the study explained that there is a positive but not significant influence between GCG and financial performance. It can be explained in more detail that the GCG variant itself consists of transparency, quality, responsibility, independence and fairness which does not have a significant influence on GCG. The company's financial performance variables use ROA, ROE and DER indicators, which also do not have a significant influence so that in the end the relationship / influence between GCG and financial performance is also not significant.